Considerations of Ethical Aspects of Control Strategies of Unowned Free-Roaming Dog Populations and the No-Kill Policy in Italy - Natoli, E. (Journal of applied animal ethics research, 2019)
The management of free-roaming dog populations is an important matter both for the local administrations that have to manage this problem and for the defenders of the animals’ rights. This review’s first objective is to analyse the legal status of the free-roaming dogs in some European countries. A second purpose of this work is to ask questions and to consider the ethical aspects of the already-existing strategies to control free-roaming dog populations. Italian Law no. 281, which was enacted in 1991, was intended to solve the problem of free-roaming dogs in Italy; at the same time, apparently in contradiction with this objective, the law called for a no-kill policy to be enforced throughout the whole national territory. Thus, for a dog that has no chances of adoption, the ethical debate has moved to the question of whether a "life imprisonment" is better than the "capital punishment". In terms of ethical aspects of control strategies of free-roaming dog populations, we believe that the Italian national law, and its regional applications, are more functional than the other laws of Westernized countries, with the appropriate measures suggested and with a more accurate control on their application.